2018
DOI: 10.5146/tjpath.2018.01429
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence in uterine tumors with ovarian sex-cord tumor resemblance: a case report and systematic review

Abstract: Objective: The aim of this study was to evaluate the prognostic factors of recurrence in uterine tumors resembling ovarian sex-cord tumors (UTROSCT) and to determine clinical-pathological characteristics, treatment options and outcome. Material and Method:An electronic literature search was conducted from 1976 to 2018. After the comprehensive evaluation and conjunction with our case, the study included 79 cases. Results:The median age at initial diagnosis was 49 years (range; 16-86 years). The age was under 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…In this review, the median age at diagnosis was 50.0 years, similar to 49-51 years in previous reviews and case series reporting UTROSCTs [10,27]. Patients under 40 years of age with UTROSCTs accounted for a small number (21.3%); therefore, fertility preservation treatment should be considered.…”
Section: Discussionsupporting
confidence: 71%
“…In this review, the median age at diagnosis was 50.0 years, similar to 49-51 years in previous reviews and case series reporting UTROSCTs [10,27]. Patients under 40 years of age with UTROSCTs accounted for a small number (21.3%); therefore, fertility preservation treatment should be considered.…”
Section: Discussionsupporting
confidence: 71%
“…Moore et al [4] observed eight cases with recurrence in 34 cases and calculated a recurrence rate of 23.5% for UTROSCT. Kavneet et al [11] reported that one out of six cases (16.7%) relapsed within 1 year of diagnosis, while Günsu et al [9] reported a recurrence rate was only 6.3%. The reason for the rst high percentage rate attributed to the inclusion of patients with metastases or occurrence in other medical institution referred to their institution for consultation which increased the proportion of relapsed patients in the medical institution.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, ESTSCLE often recurs whereas UTROSCT is usually regarded as indolent or low malignant potential neoplasm [3]. However, several cases of UTROSCT have reported recurrence and metastasis during postoperative follow-up [4][5][6][7][8][9][10][11][12][13][14]. The purpose of this article was to provide more informations on the recurrence of UTROSCT and was aware of these speci c clinicopathological parameters those were of value in predicting malignant behavior for clinicians in dealing with the subset neoplasms with aggressive characters.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review published in 2018 that evaluated prognostic factors of recurrence in UTROSCT, recurrence rates of 6.3% were found for the 79 patients evaluated. Disease-free survival is high and is associated only with the type of surgery: 86% for patients submitted to resection of the tumor alone and 96% for those submitted to total hysterectomy, both for a five-year period [ 11 ]. The UTROSCT is considered of uncertain malignant potential, and there are no formal recommendations regarding treatment [ 7 ].…”
Section: Discussionmentioning
confidence: 99%